Surface-Anchored Poly(N-isopropylacrylamide) Orthogonal Gradient Networks - Pandiyarajan, C. K. (Macromolecules, 2016)
We present a versatile synthetic route leading toward generating surface-attached polyacrylamide gels, in which the cross-link density varies continuously and gradually across the substrate in two orthogonal directions. We employ free radical polymerization to synthesize random copolymers comprising ~5% of photoactive methacrylyloxybenzophenone (MABP), ~5% of thermally active styrene sulfonyl azide (SSAz), and ~90% of N-isopropylacrylamide (NIPAAm) units. The presence of MABP and SSAz in the copolymer facilitates control over the cross-link density of the gel in an orthogonal manner using photoactivated and thermally activated cross-linking chemistries, respectively. Spectroscopic ellipsometry is employed to determine the degree of swelling of the gel in water and methanol as a function of position on the substrate. Network swelling varies continuously and gradually across the substrate and is high in regions of low gel fractions and low in regions of high gel fractions. [Image: see text]